The relationship of self-stigma with the quality of living people with HIV/AIDS (PLWHA) in WPA Turen District - Kurniawanto, Dani; Sasono, Tri Nurhudi; Kumalasari, Galuh (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
Stigma is something that unacceptable or usually condescending and degrading. Stigma and discrimination cause inhibition of HIV/AIDS prevention and treatment in the community, thus impacting psychologically and decreasing the quality of life of PLWHA. To find out the relationship between self-stigma and the quality of life of people living with HIV/AIDS (PLWHA), a study in the AIDS Concerned Residents (ACR) District of Turen. It uses a correlational analytic design with a cross-sectional approach. The number of respondents is 22 PLWHA in Turen Concerned Residents (ACR), and methods of sampling in this study are using a purposive sampling technique. From 22 respondents, the result of self-stigma on PLWHA was low, with a percentage (54.5%) and the quality of life of PLWHA living in ACR Kec. Turn is excellent, with a percentage (54.5%). The results of statistical tests show that the value of p = 0.108 and the significance level of 0.05 also obtained p > 0.05, meaning that there is no significant relationship between self-stigma and the quality of life of PLWHA. This study shows that there is no significant relationship between self-stigma and the quality of life of PLWHA. With the existence of ACR, people and HIV-AIDS sufferers in Turen District have started to eliminate existing stigma and have a good quality of life.